Participatory budget implementation models in Poland as a contribution to organizational listening to the needs of residents: diversity of practices and legislative consequences - Jurek, Krzysztof (Management and Administration Journal, 2025)
The civic budget, also known as participatory budgeting, has been implemented in Poland since 2011, when it was first introduced in the city of Sopot. Since then, the mechanism has gained considerable popularity and has been adopted by numerous local government units. In 2018, there was a significant legal change, as a result of which the civic budget became a mandatory element of governance in cities with county rights, losing its previously optional nature. This article attempts to analyze the variation in the organization and implementation of civic budgets in selected local government units in Poland. The subject of consideration are both procedural and structural differences that affect the effectiveness of this instrument of public participation. The factors determining the different implementation practices, resulting from local conditions and the specifics of individual local government units are indicated. The purpose of the study is to identify and systematize these discrepancies and assess their consequences for the quality and effectiveness of the implementation of civic budgets. The analysis presented contributes to the deepening of knowledge of implementation practices and opportunities for optimizing participatory mechanisms in the Polish local government system.